A simultaneous one pot synthesis of two fractal structures via swapping two fractal reaction kinetic states. Issue 22 (11th May 2016) - Ghosh, Subrata; Dutta, Mrinal; Ray, Kanad; Fujita, Daisuke; Bandyopadhyay, Anirban
Abstract : We introduce a new class of fractal reaction kinetics wherein two or more distinct fractal structures are synthesized as parts of a singular cascade reaction in a single chemical beaker. Abstract : We introduce a new class of fractal reaction kinetics wherein two or more distinct fractal structures are synthesized as parts of a singular cascade reaction in a single chemical beaker. Two examples: sphere ↔ spiral & triangle ↔ square fractals, grow 10 6 orders from a single dendrimer (8 nm) to the visible scale.